The capacitated lot sizing problem: a review of models and algorithms - Karimi, B.; Fatemi Ghomi, S.M.T.; Wilson, J.M. (Omega (Oxford), 2003)
Lot sizing is one of the most important and also one of the most difficult problems in production planning. This subject has been studied extensively in the literature. In this article, we consider single-level lot sizing problems, their variants and solution approaches. After introducing factors affecting formulation and the complexity of production planning problems, and introducing different variants of lot sizing and scheduling problems, we discuss single-level lot sizing problems, together with exact and heuristic approaches for their solution. We conclude with some suggestions for future research.